2007
DOI: 10.1111/j.1439-037x.2007.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Enhances the Performance of Late Sown Wheat (Triticum aestivum L.) by Improving Chilling Tolerance

Abstract: In rice–wheat systems, late sowing of wheat is the major reason of low yield. This yield reduction is principally due to lower and erratic germination, and poor crop establishment because of low temperature prevailing. The present study was conducted to explore the possibility of improving late sown wheat performance by seed priming techniques. Seed priming strategies were: on‐farm seed priming, hydropriming for 24 h, seed hardening for 12 h and osmohardening with KCl or CaCl2 for 12 h. Seed priming improved e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
138
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(154 citation statements)
references
References 32 publications
(70 reference statements)
16
138
0
Order By: Relevance
“…Petri dishes were placed at 26 ± 2°C under a 16:8 h photoperiod in an incubator (Farooq et al, 2008) until radical emergence.…”
Section: Germinationmentioning
confidence: 99%
“…Petri dishes were placed at 26 ± 2°C under a 16:8 h photoperiod in an incubator (Farooq et al, 2008) until radical emergence.…”
Section: Germinationmentioning
confidence: 99%
“…One of the most common adaptive measures that have been adopted by many countries is pre-farming seed treatments such as seed priming and coating (Hoseini et al, 2013). Seed priming is a technique by which seeds are partially hydrated to a point where germination-related metabolic processes begin but just prior to germination where radical emergence does not occur (Farooq et al, 2008). Several investigations confirmed that seed priming has many benefits including early emergence, good stand establishment, deeper roots, uniformity in emergence, initiation of reproductive organs, better competition with weed, early flowering and maturity, resistance to environmental stresses (Amin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming is used to lessen emergence time, harmonize germination, enhanced germination rate and crop establishment in a lot of horticultural (Bradford, 1986) and field crops like wheat, rice and maize Farooq et al, 2008;Rehman et al, 2011). Harris et al (1999) demonstrated that on-farm seed priming clearly enhanced early vigor and seedling establishment of maize, upland rice and chickpea, resulted in accelerated development, earlier flowering and maturity and high yields of these crops.…”
Section: Introductionmentioning
confidence: 99%